2016
DOI: 10.1002/ieam.1782
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of marine ecosystem services indicators: Experiences and lessons learned from 14 European case studies

Abstract: This article shares the experiences, observations, and discussions that occurred during the completing of an ecosystem services (ES) indicator framework to be used at European Union (EU) and Member States' level. The experience base was drawn from 3 European research projects and 14 associated case study sites that include 13 transitional-water bodies (specifically 8 coastal lagoons, 4 riverine estuaries, and 1 fjord) and 1 coastal-water ecosystem. The ES pertinent to each case study site were identified along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Based on several of the existing environmental directives (Marine Strategy Framework, Water Framework, Habitats and Birds, Bathing Water) core indicators for marine ecosystem pressures and ecosystem conditions (physical, chemical and biological quality) required for delivery of ecosystem services have been proposed (Maes et al, 2018) e.g. by Bönhke-Henrichs et al 2013; and Lillebø et al (2016). For instance, Broszeit et al, (2017, appendix B) identified 247 biodiversity indicators proposed for the monitoring of "Good Environmental Status" (GES) that could potentially also be useful ecosystem service indicators.…”
Section: Economic Valuation Frameworkmentioning
confidence: 99%
“…Based on several of the existing environmental directives (Marine Strategy Framework, Water Framework, Habitats and Birds, Bathing Water) core indicators for marine ecosystem pressures and ecosystem conditions (physical, chemical and biological quality) required for delivery of ecosystem services have been proposed (Maes et al, 2018) e.g. by Bönhke-Henrichs et al 2013; and Lillebø et al (2016). For instance, Broszeit et al, (2017, appendix B) identified 247 biodiversity indicators proposed for the monitoring of "Good Environmental Status" (GES) that could potentially also be useful ecosystem service indicators.…”
Section: Economic Valuation Frameworkmentioning
confidence: 99%
“…• the three-dimensional (or four-dimensional if time is included) nature of maritime space allowing for a greater flexibility of accommodation of various uses, • greater importance of natural factors for functioning of the maritime space (seas and oceans as functioning ecosystems producing important ecosystem services -cf. Lillebø et al (2016) such as climate change mitigation, tourism attractiveness, etc. ), • resultantly different dynamics of diffusion processes -e.g.…”
Section: Essence Of the Maritime/marine Space -A Spatial Economics Pementioning
confidence: 99%
“…There are several references reporting the fate and extended effects of 1 . For instance, environmental occurrence (Martín et al ), environmental assessment (Lillebø et al ), environmental risks (Acuña et al ), global occurrences (aus der Beek et al ), transformation products (Lonappan et al ), bioaccumulation and biomagnification (Zenker et al ), and ecotoxicological impact (Fent et al ), just to mention a few.…”
Section: Introductionmentioning
confidence: 99%